2022
DOI: 10.1210/clinem/dgac145
|View full text |Cite
|
Sign up to set email alerts
|

Corifollitropin Alfa Combined With Human Chorionic Gonadotropin in Adolescent Boys With Hypogonadotropic Hypogonadism

Abstract: Background We examined the efficacy and safety of corifollitropin alfa (CFA) combined with human chorionic gonadotropin (hCG) for the induction of testicular growth and pubertal development in adolescent boys with hypogonadotropic hypogonadism (HH). Methods This was a 64-week, multi-center, open-label, single-group study of CFA in adolescent males, 14 to <18 years of age, with HH. Seventeen participants initiated a 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…5 Exogenous testosterone treatment in young males with hypogonadism can promote premature maturation of Sertoli cells, that could negatively impact future fertility. 6,7 Early gonadotrophin therapy might be advocated in preference to testosterone replacement for young hypogonadal men. However, a prospective study of 60 male adolescents, with CH on gonadotrophin therapy for induction of spermatogenesis, showed similar spermatogenesis outcomes between those exposed to testosterone for puberty induction and those not previously exposed to testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…5 Exogenous testosterone treatment in young males with hypogonadism can promote premature maturation of Sertoli cells, that could negatively impact future fertility. 6,7 Early gonadotrophin therapy might be advocated in preference to testosterone replacement for young hypogonadal men. However, a prospective study of 60 male adolescents, with CH on gonadotrophin therapy for induction of spermatogenesis, showed similar spermatogenesis outcomes between those exposed to testosterone for puberty induction and those not previously exposed to testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Its half-life is not long enough to sustain the entire therapeutic period. Corifollitropin alfa should be administered once every 2 weeks in combination with hCG injections twice weekly in men with HH (11). We attempted to apply SAFA technology to invent long-acting biologics using FSH as a model.…”
Section: Discussionmentioning
confidence: 99%
“…Corifollitropin alfa, the longest-acting FSH available in clinics, has an approximately 1.5-to 2-fold longer elimination half-life than FSH (9). Previous studies have shown that long-acting FSH can effectively and safely replace FSH in the treatment regimen of adult men with HH desiring improved fertility (8,11).…”
Section: Introductionmentioning
confidence: 99%